A Comparative Study between Inverting and Appositional Suture Patterns for Cystotomy Closure in Dog: Rahi N. Al-Asadi and Natheria B. Khwaf - Al-Asadi, Rahi N. (The Iraqi Journal of Veterinary Medicine, 2014)
The present study is designed to evaluate two sutures pattern techniques (inverting and appositional) for urinary bladder closure following experimental cystotomy in dogs. Thirty two adult local breed males’ dogs were enrolled for this study, aged 1-3 years and weighing 18-23 kg. Dogs were randomly allocated into two equal groups. In the first group, cystotomies were closed via double-layers of continuous inverting suture pattern (Lambert and Cushing); while, in the second group, bladders incisions were closed by single-layer appositional suture pattern (simple interrupted) which did not involve the mucosa (extra-mucosal). Synthetic absorbable suture material polydiaxnone PDS 3/0 was used to close the bladder in all experimental animal groups. Surgery was done under the effect of general anesthesia using a combination of ketamine at a dose rate of 15mg/kg and xylazine at a dose 5mg/kg B.W. Dogs were premedicated by atropine sluphate at a dose 0.03mg/kg. All drugs administered intramuscularly. There were highly significant (P <0.05) differences in operative times between the two groups. In inverting group, the time was 40 ± 4.50 minutes which was higher than that recorded for appositional group 25±2.50 minutes. The animals were followedup clinically during the studied period to record the secondary complications. Results reflected hematuria n=4, swelling of the operative site n=3 and urinary incontinence n=2. These complications were transient and disappeared in a short time. Also macroscopical and microscopical examinations were performed at 3,7,14 and 21 days post-surgery. Four dogs were used for each period. The main macroscopical finding was slight to moderate adhesions n = 3 between omentum and the wall of urinary bladder in both group. Microscopical examination of urinary bladder reflected earlier urolithium formation in appositional pattern (14 days) while inverted group (21 days). In conclusion, appositional pattern is technically easier and economic. Bladder regeneration was accomplished within 14 days in comparison with inverting pattern which reflected bladder regeneration at 21 days post-surgery.